Study on physicochemical properties of bread using sourdough starter from plantain (Musa paradisiaca fa. Corniculata) flour - Mohammad T.; Hassan C.Z.; Zanariah C.W. (Faculty of Food Technology Osijek, University of Osijek, 2024)
Indexed by Scopus